Docsity
Docsity

Prepare for your exams
Prepare for your exams

Study with the several resources on Docsity


Earn points to download
Earn points to download

Earn points by helping other students or get them with a premium plan


Guidelines and tips
Guidelines and tips

Integration and Antiderivatives: Fundamental Theorem of Calculus and Substitution, Study notes of Calculus

The concepts of antiderivatives, the fundamental theorem of calculus, and the substitution rule in integral calculus. It includes definitions, theorems, examples, and properties of integrals. Students will learn how to find antiderivatives, evaluate definite integrals, and perform substitutions to solve more complex integrals.

Typology: Study notes

Pre 2010

Uploaded on 03/11/2009

koofers-user-lxm
koofers-user-lxm 🇺🇸

10 documents

1 / 4

Toggle sidebar

Related documents


Partial preview of the text

Download Integration and Antiderivatives: Fundamental Theorem of Calculus and Substitution and more Study notes Calculus in PDF only on Docsity!

  1. Antiderivative A function G is called an antiderivative for f on [a, b] iff

(i) G is continuous on [a, b] and

(ii) G′(x) = f (x) for all x in (a, b).

Notation: If G(x) is an antiderivative for f (x) on [a, b], then G(x) + C is also an antiderivative for f (x) for any constant C. We denote by

f dx, an antiderivative of f (x).

Theorem 1. If G 1 (x) and G 2 (x) are antiderivatives for f (x) on [a, b], then there exists a constant C such that G 1 (x) − G 2 (x) = C for all x in [a, b].

Example: Let n be a positive integer. Then

d dx

[

n + 1

xn+

]

= xn,

and so G(x) = (^) n^1 +1 xn+1^ is an antiderivative of the function f (x) = xn. Therefore,

xndx = (^) n+1^1 xn+1^ + C.

Example: Since

d dx

[ex] = ex, ∫ exdx = ex^ + C.

Example: We will prove later that

∫ 1 x

dx = ln|x| + C.

1

  1. Connection Between Derivative and Integral : Fundamental Theorem of Calculus Let f (t) be a continuous function [a, b]. For each x in the interval [a, b], let’s define the function F (x) by

F (x) =

∫^ x

a

f (t)dt.

Then, F (x) is continuous on x on [a, b], and for all x in the open interval (a, b),

F ′(x) = f (x).

Thus, F (x) =

∫^ x a

f (t)dt is an antiderivative of f on [a, b].

Corollary 1. Let f (t) be a continuous function [a, b]. If G is an antiderivative of f on [a, b], then ∫b

a

f (t)dt = [G(x)]ba = G(b) − G(a).

Example: Let n be a positive integer. Then, Since G(x) = (^) n+1^1 xn+1^ is an antiderivative of the function f (x) = xn, we have that

∫^2

1

xndx = [

n + 1

xn+1]^21 =

n + 1

2 n+1^ −

n + 1

1 n+1^ =

n + 1

(2n+1^ − 1).

Example: Since G(x) = ex^ is an antiderivative of the function f (x) = ex, we have that ∫^2

1

exdx = [ex]^21 = e^2 − e.

Example: Since G(x) = 2

t is an antiderivative of the function f (t) = √^1 t , we have that ∫^9

4

t

dt = [

t]^94 = 2

9 − 2

4 = 2.

Definition 1.

∫^ b a

f (t)dt = −

∫^ a b

f (t)dt.

Some Properties of Integral:

Let f and g be continuous functions on [a, b]. Let a < c < b. Also, let α be a constant.

(1)

∫^ b a

[αf (t)]dt = α

∫^ b a

f (t)dt.

(2)

∫^ b a

[f (t) + g(t)]dt =

∫^ b a

f (t)dt +

∫^ b a

g(t)dt.

(3)

∫^ b a

[f (t) − g(t)]dt =

∫^ b a

f (t)dt +

∫^ b a

g(t)dt.

(4)

∫^ b a

f (t)dt =

∫^ c a

f (t)dt +

∫^ b c

f (t)dt.

Example: Evaluate

∫^1

0

(2x − 6 x^4 + 5)dx.

Since G(x) = x^2 − 65 x^5 + 5x is an antiderivative of the function f (x) = 2x − 6 x^4 + 5, we have that

∫^1

0

(2x − 6 x^4 + 5)dx = [x^2 −

x^5 + 5x]^10 = (1^2 −

15 + (5)(1)) − (0^2 −

05 + (5)(0)) =

.

  1. Substitution Let g be a continuous function on [a, b] such that the derivative g′^ is also continuous on [a, b]. Let f be a function which is continuous on g([a, b]). Then,

(3.1)

∫^ b

a

f (g(x))g′(x)dx =

∫^ g(b)

g(a)

f (u)du,

Example: Evaluate

∫^2

1

2 x

x^2 − 1 dx.

We apply the formula (3.1). Let g(x) = x^2 − 1, and let f (x) =

x. Then we have that ∫^2

1

2 x

x^2 − 1 dx =

∫^2

1

f (g(x))g′(x)dx.

Also, F (x) = 23 x (^32) is an antiderivative for f (x) =

x. Note that, g(1) = 0, g(2) = 3, and g′(x) = 2x So by applying the formula (3.1), we get ∫^2

1

f (g(x))g′(x)dx =

∫^3

0

f (u)du =

∫^3

0

u

1 (^2) du =

[

u

3 2

] 3

0

=

[

3 (^2) − 0 3 2

]

=

3 (^2).

If we have to find an integral of the form

(3.2)

∫^ b

a

f (g(x))g′(x)dx =

∫^ g(b)

g(a)

f (u)du,

then we follow the following steps. We let u = g(x), and then du = g′(x)dx, and we change the limits of integration a and b by g(a) and G(b).

Example: Evaluate

∫^2

x=

2 xex 2 dx

Let u = x^2. Then du = 2xdx, and ∫^2

x=

2 xex^2 dx =

∫^4

u=

eudu = [eu]^41 = e^4 − e^1 = e^4 − e.